High Resolution Infrared Spectrum of the ν7+ν8 Band of the Trans-C2H2D2 Molecule; Russian Physics Journal; Vol. 59, iss. 10 - Zyatkova (Ziatkova) A. G. Anastasiya Georgievna; Aslapovskaya Yu. S. Yuliya Sergeevna; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Fomchenko A. L. Anna Leonidovna (2017, 2017)
Title screen